Degree of impactor fragmentation under collision with a regolith surface—Laboratory impact experiments of rock projectiles. (20th May 2013) - Nagaoka, Hiroki; Takasawa, Susumu; Nakamura, Akiko M.; Sangen, Kazuyoshi
Abstract Some meteorites consist of a mix of components of various parent bodies that were presumably brought together by past collisions. Impact experiments have been performed to investigate the degree of target fragmentation during such collisions. However, much less attention has been paid to the fate of the impactors. Here, we report the results of our study of the empirical relationship between the degree of projectile fragmentation and the impact conditions. Millimeter‐sized pyrophyllite and basalt projectiles were impacted onto regolith‐like sand targets and an aluminum target at velocities of up to 960 m s−1. Experiments using millimeter‐sized pyrophyllite blocks as targets were also conducted to fill the gap between this study and the previous studies of centimeter‐sized rock targets. The catastrophic disruption threshold for a projectile is defined as the energy density at which the mass of the largest fragment is the half of the original mass. The thresholds with the sand target were 4.5 ± 1.1 × 104 and 9.0 ± 1.9 × 104 J kg−1, for pyrophyllite and basalt projectiles, respectively. These values are two orders of magnitude larger than the threshold for impacts between pyrophyllite projectiles onto aluminum targets, but are qualitatively consistent with the fact that the compressive and tensile strengths of basalt are larger than those of pyrophyllite. The threshold for pyrophyllite projectiles and the aluminum target agrees with the threshold for aluminum projectiles and pyrophyllite targets within the margin of error. Consistent with a previous result, the threshold depended on the size of the rocks with a power of approximately −0.4 (Housen and Holsapple 1999). Destruction of rock projectiles occurred when the peak pressure was about ten times the tensile strength of the rocks.